1997
DOI: 10.1119/1.18496
|View full text |Cite
|
Sign up to set email alerts
|

Millikan Lecture 1996: Promoting active learning based on physics education research in introductory physics courses

Abstract: Early in his career Robert Millikan experimented with a laboratory-based method of teaching introductory physics that bears close resemblance to Workshop Physics.® In this talk, key elements of Workshop Physics are summarized. Some Workshop Physics activities are described which involve apparati that are used for rapid observations of conceptual aspects of physical phenomena as well as for equation verification experiments. Challenges are discussed that must be faced if recently developed activity-based approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 0 publications
1
53
0
1
Order By: Relevance
“…If this assumption holds than more attention is needed to guide students, and not only teachers, in coping with new pedagogical approaches. Law et al (2008) in the international study on technology integration in education have found strong correlations between teachers adoption of technology and pedagogically (instead of technically oriented) in-service arrangements for technology integration. By focusing on the TPCK framework and using strategies for professional development that have proven to be effective we have tried to design an intervention that complied with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…If this assumption holds than more attention is needed to guide students, and not only teachers, in coping with new pedagogical approaches. Law et al (2008) in the international study on technology integration in education have found strong correlations between teachers adoption of technology and pedagogically (instead of technically oriented) in-service arrangements for technology integration. By focusing on the TPCK framework and using strategies for professional development that have proven to be effective we have tried to design an intervention that complied with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the alignment of the calls in the physics education research community for a greater emphasis on developing problem solving expertise even at the expense of some factual or procedural content with the needs of students (see, e.g., [13][14][15][16]). …”
Section: B Attitudes and Motivationmentioning
confidence: 99%
“…First, to convince the students that science is an activity and to change how they learn we cannot allow the students to be passive. As such, interactive engagement (IE) [1][2][3][4][5] and Studio [6][7][8][9] teaching methods are used. In brief, IE is a method of teaching in which the students are "minds-on" and "hands-on" with the material.…”
Section: General Educationmentioning
confidence: 99%